PENGARUH PENDAPATAN PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN GARUT - Sugara, Dasep Bambang; Winarso, Widi (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2013)
Abstract - Local revenue sources of revenue coming from the local economy that aims to build the city or county and revenue receipts from local tourism sector is one of the contributors in the reception area in Garut district revenue impact of tourism on local revenues that occurred in Garut di strict that does not have a role significant but very important for the economic progress of Garut itself, therefore the tourism sector can be useful for the study discussed in a research in because of the many benefits on offer from the tourism sector, such as employment income even for relatively small revenue but sector tourism is one of the economic drivers of Garut district tax revenue is a key priority for the State to carry out the construction as compared to revenues received from other sectors of the tourism sector merupaka sector employment enough so that it can minimize unemployment in the district Garut purpose of this study to test the effect of tourism revenues to local revenues which is managed by the local government. This research uses the data in the form of tourism revenue figures from 2008 to 2012 and revenue from 2008 to 2012 were sourced from the finance office financial and asset management income, and the Department of tourism and culture Garut regency.The method used is descriptive analysis of the tourism revenue source revenue Garut regency, tool used remedy is a simple linear regression research, results of this study showed that the influence that caused to revenue from tourism revenue is there but not significant when viewed over a reliance on tourism for revenue source revenue. Keywords: tourism revenue, local revenue